Bone Metastases from Prostate Cancer Biology, Diagnosis and Management - Bertoldo, Francesco; Boccardo, Francesco; Bombardieri, Emilio; Evangelista, Laura; Valdagni, Riccardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents up-to-date information on one of the hottest topics in prostate cancer, namely bone metastases. The most recent developments with respect to biology, pathology, diagnosis, and treatment are described, providing readers with an excellent understanding of the mechanisms of metastasis formation, the characteristics of metastases, their aggressiveness, and prognostic factors for treatment response. The coverage includes discussion of all of the best available options (laboratory, radiology, and nuclear medicine) for achieving early diagnosis and both established and novel therapeutic approaches. Detailed information is provided on hormonal manipulations, bone-targeted agents, vaccines, taxanes, and other treatments that are enriching the therapeutic armamentarium. The editors can be considered leaders in the field, with great experience in diagnostic and clinical oncology and research, and the authors are experts in diverse specialties. This ensures a multidisciplinary approach, mirroring the current situation in which treatment in patients with bone metastases is undertaken by a team of specialists and health professionals in a variety of fields.
Biology and pathophysiology of bone metastases -- Markers of bone turnover -- Bone homing and metastasis -- Markers of prostate cancer -- Circulating cells -- Radiological assessment of bone metastases -- Nuclear Medicine: bone target imaging -- Nuclear Medicine: cancer and receptor target imaging -- Hormonal therapy -- Chemotherapy -- Combinations of hormonal therapy and chemotherapy -- Surgery -- Radiotherapy -- Bone-targeted agents -- Bone seeking radionuclide for therapy -- New frontiers in treatments -- Approaches for the assessment of response to therapies -- From Symptom control to pain palliation -- Economic impact of prostate cancer bone metastases -- Multidisciplinary approach. .
Keywords: Medicine; Nuclear medicine; Radiotherapy; Oncology; Orthopedics; Pathology; Urology; Medicine & Public Health; Oncology; Urology; Nuclear medicine; Radiotherapy; Orthopedics; Pathology